Kidnapped - Stevenson, Robert Louis, 1850-1894.; Hite, Sid. (New York : Scholastic, 1977)
In 1751 in Scotland, cheated out of his inheritance by a greedy uncle who has him kidnapped and put on a ship to the Carolinas, seventeen-year-old David Balfour escapes to the Highlands with the help of the Jacobite Alan Breck Stewart and there encounters further danger and intrigue as he attempts to clear his name and regain his property.
Faculty.
Keywords: Kidnapping victims -- Fiction; Disinheritance -- Fiction; Teenage boys -- Fiction; Jacobites -- Fiction; Scotland -- History -- 18th century -- Fiction; Historical fiction